Aortic Stiffness, Pulse Pressure, and Cerebral Pulsatility Progress Despite Best Medical Management: The OXVASC Cohort. Issue 4 (2nd December 2021) - Webb, Alastair J.S.; Lawson, Amy; Wartolowska, Karolina; Mazzucco, Sara; Rothwell, Peter M.; ,
Abstract : Background: Increased cerebral arterial pulsatility is associated with cerebral small vessel disease, recurrent stroke, and dementia despite the best medical treatment. However, no study has identified the rates and determinants of progression of arterial stiffness and pulsatility. Methods: In consecutive patients within 6 weeks of transient ischemic attack or nondisabling stroke (OXVASC [Oxford Vascular Study]), arterial stiffness (pulse wave velocity [PWV]) and aortic systolic, aortic diastolic, and aortic pulse pressures (aoPP) were measured by applanation tonometry (Sphygmocor), while middle cerebral artery (MCA) peak (MCA-PSV) and trough (MCA-EDV) flow velocity and Gosling pulsatility index (PI; MCA-PI) were measured by transcranial ultrasound (transcranial Doppler, DWL Doppler Box). Repeat assessments were performed at the 5-year follow-up visit after intensive medical treatment and agreement determined by intraclass correlation coefficients. Rates of progression and their determinants, stratified by age and sex, were determined by mixed-effects linear models, adjusted for age, sex, and cardiovascular risk factors. Results: In 188 surviving, eligible patients with repeat assessments after a median of 5.8 years. PWV, aoPP, and MCA-PI were highly reproducible (intraclass correlation coefficients, 0.71, 0.59, and 0.65, respectively), with progression of PWV (2.4%; P <0.0001) and aoPP (3.5%; P <0.0001) but not significantly for MCA-PI overall (0.93; P =0.22). However, PWV increased at a faster rate with increasing age (0.009 m/s per y/y; P <0.0001), while aoPP and MCA-PI increased significantly above the age of 55 years (aoPP, P <0.0001; MCA-PI, P =0.009). Higher aortic systolic blood pressure and diastolic blood pressure predicted a greater rate of progression of PWV and aoPP, but not MCA-PI, although current MCA-PI was particularly strongly associated with concurrent aoPP ( P <0.001). Conclusions: Arterial pulsatility and aortic stiffness progressed significantly after 55 years of age despite the best medical treatment. Progression of stiffness and aoPP was determined by high blood pressure, but MCA-PI predominantly reflected current aoPP. Treatments targetting cerebral pulsatility may need to principally target aortic stiffness and pulse pressure to have the potential to prevent cerebral small vessel disease.